Pengaruh Online Review Gofood Terhadap Permintaan Produk Makanan Di Kabupaten Mojokerto - Anzilina Dwi Salsabila; Shanti Nugroho Sulistyowati (STIE PGRI Dewantara Jombang, 2025)
The purpose of this study is to analyze the influence of online reviews on the demand for food products through the GoFood service in Mojokerto Regency. The online reviews examined include star ratings and consumer comment reviews. The research employed a quantitative approach with a survey of 384 GoFood users in Sooko District. A probability random sampling technique was used in the sampling process, and the data were collected through a questionnaire based on indicators of online reviews and product demand. Simple linear regression was applied in the data analysis process. The results indicate that online reviews have a positive and significant effect on the demand for food products. These findings reinforce that online star ratings and comment reviews greatly influence consumer purchasing decisions in the digital era.